Implementação e utilização de telefonia VoIP na empresa Comercial Pato Branco Ltda - Gemelli, Alberto (2018)
As a mean of communication the VoIP system has been showing itself as an effective and economic way when it comes to telephony in medium and large companies. This work refers to the study of the implementation of a VoIP system in the headquarters and branch at the ref erred organization. Considering the result, it’s able to come to a conclusion which due to fixed and mobile telephony plans currently used, the project haven’t become viable in its totality, being implemented only for the technical support department. With the expansion of the company, it’s expected a larger usage with IP terminals and calls among the headquarters and the branches.